(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This article discusses the state of use of renewable energy sources in the Republic of Uzbekistan, current issues in ensuring sustainable development in the energy sector, and the problems of improving the system of personnel training in engineering. The authors analyze the didactic conditions for the use of digital technologies in the process of energy education and justify the need to strengthen the integration of education and production.